The Predictive Value of N-Terminal Probrain Natriuretic Peptide for Infection in Patients With Acute Myocardial Infarction - Dai, YiNing; Wan, XiaoLiang; Liu, Can; Duan, ChongYang; Shao, Shuai; Chen, HongHuan; Wang, Litao; Lin, JiJin; Xue, Ling; Chen, JiYan; He, PengCheng; Liu, YuanHui; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Infections increase the risk of poor outcomes in patients with ST-elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). However, predicting patients at a high risk of developing infection remains unclear. Moreover, the value of N-terminal probrain natriuretic peptide (NT-proBNP) for predicting infection is still unknown. Thus, we aimed to assess the relationship between NT-proBNP and the following development of infection, and clinical adverse outcomes in patients with STEMI undergoing PCI. Methods: STEMI patients undergoing PCI were consecutively enrolled from January 2010 to July 2016 and divided into groups according to baseline NT-proBNP levels: tertiles T1 (<988 pg/mL), T2 (988-3520 pg/mL), and T3 (≥ 3520 pg/mL). The primary endpoint was in-hospital infection. Results: A total of 182 (27%) patients developed in-hospital infection. The incidence of infection increased from T1 to T3 (10.5%, 17.7%, 54.5%, P<0.001). NT-proBNP was an independent risk factor (adjusted odds ratio=1.39, 95% confidence interval (CI)=1.12-1.73, P=0.003) and presented accurately predicting infection (area under curve=0.774). Multivariate cox analysis showed that NT-proBNP was a signiﬁcant risk factor for major adverse clinical events (MACE) at follow-up (adjusted HR=1.92, 95% CI=1.61-2.29, P<0.001). Conclusion: The baseline NT-proBNP level has a good predictive value for infection and MACE in STEMI patients undergoing PCI.